Cost-Effectiveness of ACTH vs. ACT Chemotherapy Regimens at RSUP Dr. M. Djamil - Nadiatul Aulia Zahara Rizki; Dita Permatasari; Fitri Handayani; Ridho Asra; Najmiatul Fitria (Fakultas Farmasi Universitas Andalas, 2025)
Introduction: Breast cancer is one of the most common cancers and is often diagnosed at a late stage, especially in Indonesia. This highlights the need for cost-effective treatment options. ACT (Adriamycin, Cyclophosphamide, and Taxane) and ACTH (ACT plus Herceptin/Trastuzumab) are used chemotherapy regimens, but studies comparing their cost-effectiveness are still limited. This study aimed to evaluate the cost-effectiveness of ACT versus ACTH for breast cancer treatment using tumor volume reduction. Method: A retrospective cost-effectiveness study was carried out at Dr. M. Djamil Hospital by comparing direct medical costs and tumor volume changes in breast cancer patients treated with ACT or ACTH regimens. Effectiveness was based on the average change in tumor volume, and cost-effectiveness was evaluated using the Incremental Cost-Effectiveness Ratio (ICER). Results: The mean tumor volume reduction in the ACT group was 2820.85 ± 11190.42 cm³, and significantly higher at 9273.50 ± 60101.33 cm³ in ACTH, although the difference was not statistically significant (p = 0.614). The average direct medical cost for ACTH was IDR 67,138,579, compared to IDR 13,005,027 for ACT. The ICER calculation resulted in IDR-838,935 per cm³ of tumor reduction, while the negative ICER might suggest cost savings, it does not imply that ACTH is a dominant strategy indicating that ACTH incurred a higher cost with less effectiveness per unit of tumor reduction than ACT. Conclusion: The high associated cost leads to a negative ICER, suggesting that ACT may be more cost-effective in this setting. These findings are critical for optimizing chemotherapy choices within limited healthcare budgets.